Modeling the current habitat suitability of genus Selaginella in Java, Indonesia - AHMAD DWI SETYAWAN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; MUHAMMAD NUR SULTON; GILANG DWI NUGROHO; ILYAS NURSAMSI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Setyawan AD, Sutarno, Sugiyarto, Sunarto, Sulton MN, Nugroho GD, Nursamsi I. 2026. Modeling the current habitat suitability of genus Selaginella in Java, Indonesia. Biodiversitas 27 (3): d270342. https://doi.org/10.13057/biodiv/d270342. Species Distribution Models (SDMs) have become essential tools in ecology, biogeography, biodiversity conservation, and natural resource management. Among the available approaches, Maximum Entropy (MaxEnt) is widely used to predict species distributions based on occurrence records and environmental variables. Selaginella (Selaginellaceae) is a lycophyte genus that depends on moist environmental conditions because free water is required for fertilization, making its distribution closely associated with climatic factors. This study aimed to model the current habitat suitability of Selaginella in Java, Indonesia, and to identify the climatic and topographic variables influencing its distribution. Occurrence records were compiled from field surveys, herbarium collections, and biodiversity databases, yielding 1,962 filtered records representing 21 accepted species and one unidentified accession. After data cleaning and 5-km spatial thinning, 811 occurrence records from 434 localities were retained for modeling. Twenty-two environmental predictors were evaluated, and model performance was assessed using cross-validation and Jackknife analyses. The MaxEnt model achieved good predictive performance (AUC = 0.811), indicating reasonably reliable discrimination between suitable and unsuitable habitats. Habitat suitability was primarily influenced by elevation (28.9%), Solar Radiation in April (19.4%), Precipitation of the Warmest Quarter (17.2%), and Annual Precipitation (17.0%). Response curves indicated optimal suitability at elevations of approximately 1,000–1,500 m above sea level under humid climatic conditions with high annual rainfall. Suitable habitats covered approximately 63,870.41 km², representing 49.19% of Java’s land area, and were concentrated in mountainous regions of West Java, Central Java, East Java, and the Dieng Plateau. These findings demonstrate that climatic and topographic conditions strongly influence the distribution of Selaginella in Java and provide a valuable baseline for conservation planning, habitat management, and future climate-change assessments.